Fault Detection in Printed Circuit Board (PCB) using Image Subtraction Method - Dr. Avinash S; Dr. Prathapchandra; Mr. Ramachandra, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
Fault detection in PCBs is a important task in the electronics industry to ensure the consistency and performance of electronic devices. One common approach for detecting defects in PCBs is the subtraction method, which involves subtracting a reference image of a defect- free PCB from an image of a PCB with defects. The resulting image gives the differences between the two images, making it easier to detect and classify defects. In this work, a defect detection system for PCBs using the subtraction method using MATLAB is proposed. The research work uses publicly available PCB defect datasets to train and test the system. The work consists of image pre-processing, image subtraction, and defect detection.